Long flame coal-based hard carbon negative electrode material, preparation method and sodium ion battery

The long flame coal is fully oxidized at multiple points by a combined method of static and dynamic oxidation, which solves the problems of poor oxidation uniformity and insufficient oxidation depth of raw coal, and prepares a long flame coal-based hard carbon negative electrode material with high reversible capacity and excellent cycling performance.

CN119873790APending Publication Date: 2025-04-25CHINA COAL HUALI XINJIANG CARBON TECH CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510063357.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the oxidation process of raw coal is oxidized in a single process, with poor oxidation uniformity and insufficient oxidation depth, resulting in a low sodium storage capacity of the prepared sodium electrohard carbon negative electrode material.

Method used

The combined method of static oxidation and dynamic oxidation is used to fully oxidize the long flame coal at multiple points to improve the oxidation uniformity and oxidation depth of the coal particles, and prepare the long flame coal-based hard carbon negative electrode material through carbonization treatment.

Benefits of technology

All-round oxidation of long flame coal is achieved, the reactive activity and sodium storage capacity of the material are improved, and high reversible capacity, high first-time Coulomb efficiency and excellent circulation performance are shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873790A_ABST
    Figure CN119873790A_ABST
Patent Text Reader

Abstract

The invention provides a long flame coal-based hard carbon negative electrode material, a preparation method and a sodium ion battery, and belongs to the technical field of battery materials. The preparation method of the long flame coal-based hard carbon negative electrode material comprises the following steps: sequentially carrying out static oxidation treatment, dynamic oxidation treatment and carbonization treatment on long flame coal. According to the invention, a static and dynamic combined oxidation method is used for the long flame coal, all-directional and multi-point full oxidation of the long flame coal can be realized, the oxidation uniformity and the oxidation depth in coal particles are improved, and the long flame coal-based hard carbon negative electrode material prepared based on the method has relatively high reaction activity and is suitable for industrial production. And the oxygen-grafted sites in the particles can promote the formation of a playing card house structure, so that the particles show high reversible capacity, high first coulombic efficiency and excellent cycle performance. In the industrial amplification process, the preparation method is simple and easy to implement, raw materials can be prevented from being crushed into fine particles in one step, and the problems that one-step oxidation is poor in uniformity and insufficient in oxidation depth are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a long flame coal-based hard carbon negative electrode material, a preparation method and a sodium ion battery. Background Art

[0002] With the continuous development of energy storage technology, the demand for high-performance batteries is growing. Sodium-ion batteries have broad application prospects in large-scale energy storage and other fields due to their abundant sodium resources and relatively low cost. However, the performance of sodium-ion batteries still needs to be further improved, especially the performance of negative electrode materials plays a key role in the overall performance of sodium-ion batteries.

[0003] However, graphite, the traditional negative electrode material for lithium-ion batteries, exhibits low sodium storage capacity and poor rate performance in sodium-ion batteries. This is because the radius of sodium ions is larger than that of lithium ions, making it difficult for them to be effectively embedded and extracted between graphite layers.

[0004] Hard carbon negative electrode materials have a larger pore structure and can accommodate more sodium ions, which makes them have higher sodium storage capacity, good cycle stability, and excellent rate performance, making them a research hotspot for sodium ion battery negative electrode materials.

[0005] As the carbon source with the highest carbon yield and the lowest raw material price, coal is one of the preferred materials for preparing hard carbon materials.

[0006] Coal is a low-cost natural material with a complex three-dimensional (3D) cross-linked network structure composed of an aromatic structure as a skeleton and an alkyl chain structure as a filler. The unique molecular structure characteristics give coal great potential for synthesizing hard carbon negative electrode materials with excellent performance.

[0007] However, the current oxidation process of raw coal is single-process oxidation, with poor oxidation uniformity and insufficient oxidation depth. Therefore, the direct preparation of sodium electric hard carbon negative electrode materials still has the problem of low capacity.

[0008] Therefore, how to achieve deep oxidation modification of raw coal, improve the oxidation uniformity inside coal particles, and obtain high-performance long flame coal-based hard carbon negative electrode materials is a technical problem that needs to be solved urgently. Summary of the invention

[0009] In view of the deficiencies in the prior art, the present invention aims to provide a long flame coal-based hard carbon negative electrode material, a preparation method and a sodium ion battery with high reversible capacity, high first coulombic efficiency and excellent cycle performance.

[0010] One of the purposes of the present invention is to provide a method for preparing a long flame coal-based hard carbon negative electrode material, the preparation method comprising: Firstly, static oxidation treatment is performed on long flame coal to obtain static oxidation material; Then, the static oxidizing material is subjected to dynamic oxidation treatment to obtain a long flame coal-based hard carbon negative electrode material precursor; Then, the long flame coal-based hard carbon negative electrode material precursor is carbonized to obtain the long flame coal-based hard carbon negative electrode material; Wherein, the long flame coal is in powder form. Preferably, the static oxidation treatment adopts a flat plate method, including: firstly spreading the long flame coal flat on a medium plate, and then placing it in a static sintering device for static oxidation treatment.

[0011] Preferably, the layer thickness of the long flame coal after being laid flat is 3-4 mm.

[0012] Preferably, the static oxidation treatment process is carried out in an oxygen-containing atmosphere.

[0013] Preferably, the oxygen-containing atmosphere of the static oxidation treatment comprises an inert gas and an oxidizing gas.

[0014] Preferably, the volume fraction of the inert gas is 60-85%.

[0015] Preferably, the temperature of the static oxidation treatment is 100-250°C, the heating rate is 1-5°C / min, and the constant temperature time is 2-3h.

[0016] Preferably, the dynamic oxidation treatment includes primary treatment, secondary treatment and tertiary treatment.

[0017] Preferably, the temperature of the primary treatment is less than the temperature of the secondary treatment and less than the temperature of the tertiary treatment.

[0018] Preferably, the temperature of the primary treatment is 250-300°C and the time is 40-80 minutes.

[0019] Preferably, the temperature of the secondary treatment is 300-350° C. and the time is 40-80 min.

[0020] Preferably, the temperature of the tertiary treatment is 350-400° C. and the time is 40-80 min.

[0021] Preferably, the dynamic oxidation treatment process is carried out in a dynamic oxidation device.

[0022] Preferably, the material filling rate of the dynamic oxidation equipment is 10-15%.

[0023] Preferably, the rotation speed of the dynamic oxidation device is 0.5-2 rpm.

[0024] Preferably, the dynamic oxidation treatment is performed in an oxygen-containing atmosphere.

[0025] Preferably, the temperature of the carbonization treatment is 1200-1600° C., and the time of the carbonization treatment is 1-10 h.

[0026] Preferably, the carbonization treatment is carried out in an inert atmosphere.

[0027] The second object of the present invention is to provide a long flame coal-based hard carbon negative electrode material, wherein the long flame coal-based hard carbon negative electrode material is prepared by the preparation method as described above.

[0028] A third object of the present invention is to provide a sodium ion battery, which comprises the long flame coal-based hard carbon negative electrode material as described above.

[0029] The beneficial effects of the present invention include: (1) The present invention uses a static and dynamic combined oxidation method for long flame coal, which can achieve full oxidation of long flame coal in all directions and at multiple points, and improve the oxidation uniformity and oxidation depth inside the coal particles. The long flame coal-based hard carbon negative electrode material prepared based on this method has high reactivity, and the sites of grafted oxygen inside the particles can promote the formation of a "house of cards" structure, so that it exhibits high reversible capacity, high first coulombic efficiency and excellent cycle performance.

[0030] (2) The preparation method provided by the present invention is simple and easy to implement during industrial scale-up, and solves the problems of poor one-step oxidation uniformity and insufficient oxidation depth. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A flow chart of the preparation process of the long flame coal-based hard carbon negative electrode material provided in Example 1; Figure 2 This is the SEM image of the long flame coal-based hard carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0032] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details, but with other methods, components, materials, etc.

[0033] Unless otherwise required herein, the words "include" and "comprising" should be interpreted as having an open and inclusive meaning, ie, "including but not limited to."

[0034] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification mean that the specific referenced elements, structures or features described in connection with the embodiment are included in at least one embodiment. Therefore, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. In addition, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.

[0035] According to a first aspect of the present invention, a method for preparing a long flame coal-based hard carbon negative electrode material is provided, the preparation method comprising: Firstly, static oxidation treatment is performed on long flame coal to obtain static oxidation material; Then, the static oxidizing material is subjected to dynamic oxidation treatment to obtain a long flame coal-based hard carbon negative electrode material precursor; Then, the long flame coal-based hard carbon negative electrode material precursor is carbonized to obtain the long flame coal-based hard carbon negative electrode material; Wherein, the long flame coal is in powder form. In the present invention, long flame coal is used as raw material, and the use of long flame coal has the following beneficial effects: On the one hand, long flame coal has a rich pore structure, high porosity, and uneven pore volume distribution, with large pores accounting for the majority, accounting for about 40%, and transition pores and micropores dominating the pore specific surface area, accounting for about 97%. This rich pore structure provides a large amount of space and channels for the storage and transmission of sodium ions, which is conducive to improving the sodium storage capacity and rate performance of sodium storage negative electrode materials. During the charge and discharge process, sodium ions can quickly embed and escape from the pores, thereby achieving efficient energy storage and release.

[0036] Secondly, the basic structural unit of long flame coal is conducive to reaction. The basic structural unit of long flame coal is composed of benzene ring, alicyclic ring, hydrogenated aromatic ring and heterocyclic ring, etc., and oxygen-containing groups and alkyl side chains are connected around the benzene ring. After proper treatment, these structures can interact with sodium ions to form a stable sodium storage structure and improve the sodium storage capacity of the material.

[0037] Thirdly, long flame coal is rich in oxygen-containing functional groups, such as phenolic hydroxyl and carbonyl groups. These functional groups can increase the surface activity of the material, improve the reaction activity with sodium ions, and facilitate the adsorption and storage of sodium ions. At the same time, oxygen-containing functional groups can also enhance the hydrophilicity of the material, allowing the electrolyte to better infiltrate the material and improve the ion transmission efficiency; The sulfur- and nitrogen-containing functional groups in long flame coal can synergize with sodium ions to further improve the sodium storage performance of the material. The presence of these functional groups can also improve the conductivity of the material, reduce internal resistance, and improve the charge and discharge efficiency of the battery.

[0038] Fourthly, the volatile matter of long flame coal is particularly high, which makes it easier to carry out chemical reactions and structural adjustments in the process of preparing sodium storage negative electrode materials. The high volatile matter and the pore structure and rich functional groups of long flame coal work together to further optimize the pore structure and surface properties of long flame coal in the subsequent static oxidation, dynamic oxidation and carbonization processes, forming a more stable carbon structure and improving the sodium storage performance and cycle stability of the material.

[0039] In the present invention, firstly, static oxidation treatment is performed on the long flame coal, and preliminary oxidation modification is performed on the long flame coal. Firstly, oxidation reaction occurs on the surface and part of the internal structure of the long flame coal. In an oxygen-containing atmosphere, the oxidizing gas reacts with carbon, hydrogen and other elements in the long flame coal, and further introduces oxygen-containing functional groups, such as hydroxyl, carboxyl, etc. These functional groups increase the surface activity of the long flame coal, and provide more abundant reaction sites for subsequent deep oxidation and carbonization treatment.

[0040] Then, the long flame coal is subjected to dynamic oxidation treatment, and the long flame coal is deeply oxidized and modified to further destroy the molecular structure of the long flame coal, form more pores and defects, and increase the storage sites of sodium ions. During the dynamic oxidation process, the material is constantly moving in the dynamic oxidation equipment and is fully in contact with the oxidizing gas, ensuring the depth and uniformity of oxidation.

[0041] Finally, the long flame coal-based hard carbon negative electrode material precursor that has undergone static and dynamic oxidation treatment is carbonized, and the carbon atoms in the precursor are rearranged to form a unique structure of hard carbon.

[0042] The use of static and dynamic combined oxidation methods for long flame coal can achieve full oxidation of the long flame coal in all directions and at multiple points, improve the oxidation uniformity and oxidation depth inside the coal particles, and then the long flame coal-based hard carbon negative electrode material prepared by carbonization treatment has high reactivity, and the sites of grafted oxygen inside the particles can promote the formation of a "house of cards" structure, so that it exhibits high reversible capacity, high first coulombic efficiency and excellent cycle performance.

[0043] In addition, long flame coal is a rich coal resource with a relatively low price. The static and dynamic oxidation treatment and carbonization treatment processes used in this preparation method are relatively simple, and the equipment requirements are not high, which is conducive to reducing production costs. At the same time, the use of coal resources to prepare hard carbon negative electrode materials reduces dependence on scarce resources and has the advantage of sustainable development.

[0044] In a preferred embodiment of the present invention, the static oxidation treatment adopts a flat plate method, including: firstly, spreading the long flame coal flat on a medium plate, and then placing it in a static sintering device for static oxidation treatment.

[0045] Specifically, the dielectric plate includes one or more of a stainless steel plate, a cast iron plate, a ceramic plate or mullite.

[0046] Preferably, the dielectric sheet has a thickness of 8-15 mm, for example, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm or 15 mm, and any value between any two of the above.

[0047] Preferably, the static sintering equipment includes any one of a mesh belt furnace, a coke removal furnace, a sintering furnace or a box furnace, or a combination of at least two of them.

[0048] Preferably, the long flame coal feedstock is first pulverized to obtain coal particles with a particle size D50 of 20-50 μm, and then subjected to static oxidation treatment. The particle size D50 of the coal particles is, for example, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, and any point value between the above two.

[0049] In the present invention, the particle size D50 of the long flame coal is controlled to be 20-50 μm, which can fully oxidize the surface of the material on the one hand, and control the depth of the oxidation reaction of the internal structure on the other hand.

[0050] Preferably, the layer thickness of the long flame coal after being laid flat is 3-4 mm, for example, 3 mm, 3.2 mm, 3.4 mm, 3.6 mm, 3.8 mm or 4 mm, and any point value between any two of the above.

[0051] In the present invention, during the static oxidation treatment process, the long flame coal is spread to a thickness of 3-4 mm, so that the long flame coal can be fully contacted with the oxygen-containing atmosphere and local over-oxidation of the long flame coal can be avoided during the oxidation process. The layer thickness of 3-4 mm can balance the rate and degree of the oxidation reaction to a certain extent, so that the long flame coal can undergo sufficient oxidation reaction during the static oxidation treatment process to introduce the required oxygen-containing functional groups, while not destroying its overall structure due to over-oxidation.

[0052] In a preferred embodiment of the present invention, the static oxidation treatment process is carried out in an oxygen-containing atmosphere.

[0053] Preferably, the oxygen-containing atmosphere of the static oxidation treatment comprises an inert gas and an oxidizing gas.

[0054] Preferably, the volume fraction of the inert gas is 60-85%, for example, 85%, 80%, 75%, 70%, 65% or 60%, and any value therebetween.

[0055] In the present invention, a combination of inert gas and oxidizing gas is used as the oxygen-containing gas for static oxidation treatment. On the one hand, it is helpful for sufficient oxidation at multiple points and timely taking away volatile gases such as tar released during the oxidation process; on the other hand, it is helpful for regulating the oxidation reaction rate and making the reaction proceed more smoothly. The presence of inert gas can also promote gas mixing and diffusion, making the oxidizing gas more evenly distributed around the long flame coal, thereby improving the overall uniformity of long flame coal oxidation and providing a good foundation for the subsequent preparation of high-performance hard carbon negative electrode materials.

[0056] In a preferred embodiment of the present invention, the temperature of the static oxidation treatment is 100-250°C, for example, 100°C, 120°C, 150°C, 170°C, 200°C, 230°C or 250°C, and any point value therebetween.

[0057] In the present invention, at a temperature of 100-250°C, the structure of the long flame coal is relatively stable, and it can maintain its basic three-dimensional cross-linked network structure while undergoing oxidation reaction, providing a good structural basis for subsequent carbonization treatment. The long flame coal can also be oxidized to a suitable degree during the static oxidation process to form a certain number of oxygen-containing functional groups, and avoid some unnecessary side reactions, such as pyrolysis reactions, so that the oxidation reaction is more controllable. If the temperature of the static oxidation treatment is too low, the oxidation effect will be insufficient and the electrochemical properties of the hard carbon will be poor; if the temperature of the static oxidation treatment is too high, ablation will occur.

[0058] Preferably, the heating rate of the static oxidation treatment is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, and any point value between the above two.

[0059] In the present invention, a slow heating rate can ensure that the long flame coal is heated evenly during the static oxidation process, and reduce the thermal shock to the long flame coal during the heating process, thereby avoiding sudden changes in the structure of the long flame coal, cracks or other defects that affect its performance, and can also make the molecular structure of the long flame coal gradually adapt to temperature changes, reduce the generation of thermal stress, and maintain the structural stability of the material.

[0060] Preferably, the constant temperature time of the static oxidation treatment is 2-3 h, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, and any value between the above two.

[0061] In a preferred embodiment of the present invention, the dynamic oxidation treatment includes primary treatment, secondary treatment and tertiary treatment, and the temperature of the primary treatment is less than the temperature of the secondary treatment and less than the temperature of the tertiary treatment.

[0062] In the present invention, the dynamic oxidation treatment is performed by adopting the above-mentioned multi-stage treatment method, which can more fully oxidize the inside of the particles, increase the oxidation depth, and obtain a uniform and comprehensive oxidation effect.

[0063] This is because, by setting different temperature stages, on the one hand, the progress of the oxidation reaction can be precisely controlled. In the primary treatment stage at a lower temperature, the oxidation reaction is relatively mild, and the surface of the long flame coal and the parts that are more easily oxidized are mainly initially oxidized. As the temperature gradually increases, the intensity of the oxidation reaction gradually increases, and it can penetrate into the internal structure of the long flame coal to achieve more thorough oxidation. This gradual heating method can avoid excessive oxidation or uneven oxidation that may be caused by one-time high-temperature oxidation, making the oxidation process more controllable and improving the quality and uniformity of oxidation; Secondly, the treatment at different temperature stages can make the long flame coal form an oxide layer with a gradient structure. The oxide layer formed by the primary treatment is relatively shallow, mainly introducing some preliminary oxygen-containing functional groups. The secondary and tertiary treatments further deepen the degree of oxidation, forming a richer pore structure and more types of oxygen-containing functional groups. The oxide layers of different depths can provide different sodium ion storage sites, improve the sodium storage capacity, and the gradient structure also helps to enhance the stability and cycle performance of the material. Third, it helps to optimize the pore structure. At the lower temperature of the primary treatment, the long flame coal begins to undergo oxidation reaction, some chemical bonds are destroyed, and some preliminary pore structures are formed. The mild oxidation in the low temperature stage can avoid excessive expansion or collapse of the pores, making the formed pore structure relatively stable; in the medium temperature stage of the secondary treatment, the oxidation reaction is further intensified, more carbon atoms are oxidized, and more pore expansion is formed. Appropriate pore expansion is conducive to increasing the contact area between sodium ions and materials and improving sodium storage performance. At the same time, medium temperature treatment can also make the pore structure more uniform and enhance the conductivity and ion transport performance of the material. During the high-temperature stage of the tertiary treatment, the oxidation reaction reaches a relatively high intensity. The high temperature can make the carbon atoms on the pore walls arrange more closely, enhancing the stability of the pores. At the same time, some unstable structures generated during the oxidation process will also be adjusted and optimized under high temperature, ensuring the structural stability of the material and the long-term reliability of its performance.

[0064] In a preferred embodiment of the present invention, the temperature of the primary treatment is 250-300°C, for example, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, and any value therebetween; the time is 40-80min, for example, 40min, 50min, 60min, 70min or 80min, and any value therebetween.

[0065] In the present invention, if the temperature of the primary treatment is too low, the reactivity of the particles with oxygen is low, which may easily lead to poor oxidation effect.

[0066] Preferably, the temperature of the secondary treatment is 300-350°C, for example, 300°C, 310°C, 320°C, 330°C, 340°C or 350°C, and any value therebetween; the time is 40-80min, for example, 40min, 50min, 60min, 70min or 80min, and any value therebetween.

[0067] Preferably, the temperature of the tertiary treatment is 350-400°C, for example, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, and any value between any two of the above; the time is 40-80min, for example, 40min, 50min, 60min, 70min or 80min, and any value between any two of the above.

[0068] In the present invention, if the temperature of the tertiary treatment is too high, ablation of the material is likely to occur, affecting the preparation of hard carbon.

[0069] In a preferred embodiment of the present invention, the dynamic oxidation treatment process is carried out in a dynamic oxidation device.

[0070] In the present invention, the dynamic oxidation equipment includes a rotary kiln. Dynamic oxidation can completely solve the part that is not oxidized in static oxidation and simultaneously solve the problem of insufficient oxidation depth.

[0071] Preferably, the material filling rate of the dynamic oxidation device is 10-15%, for example, 10%, 11%, 12%, 13%, 14% or 15%, and any point value therebetween.

[0072] In the present invention, if the material filling rate of the dynamic oxidation device is too low, the feed capacity will be affected, resulting in low capacity; if the material filling rate of the dynamic oxidation device is too high, the material will accumulate and the oxidation effect will be poor.

[0073] Preferably, the rotation speed of the dynamic oxidation device is 0.5-2 rpm, for example, 0.5 rpm, 1 rpm, 1.5 rpm or 2 rpm, or any point value between any two of the above.

[0074] In the present invention, if the rotation speed is too low, the material is not turned well and the oxidation effect is poor; if the rotation speed is too high, dust is easily generated, the material is carried away by the gas, and the material blowing phenomenon occurs.

[0075] Preferably, the dynamic oxidation treatment is performed in an oxygen-containing atmosphere.

[0076] Specifically, the oxygen-containing atmosphere of the dynamic oxidation treatment includes an inert gas and an oxidizing gas.

[0077] Preferably, the volume fraction of the inert gas in the dynamic oxidation treatment is 80-90%, for example, 80%, 82%, 84%, 86%, 88% or 90%, and any value therebetween.

[0078] Preferably, the volume fraction of the inert gas in the dynamic oxidation treatment is greater than the volume fraction of the inert gas in the static oxidation treatment.

[0079] In the present invention, oxidation has already occurred on the surface of the static oxidation material. During the dynamic oxidation treatment, the oxygen content is reduced, which is beneficial for oxygen and carbon to form more pore structures in a relatively inert environment, and is beneficial for improving the capacity of the hard carbon negative electrode material. At the same time, under relatively inert conditions, while the material is oxidized to form pores, there is also a closed-cell shrinkage phenomenon, which makes the formed hard carbon have structural shrinkage behavior and form more through-pore structures, which is beneficial to the rate properties of the hard carbon.

[0080] Preferably, the preparation method also includes a step of crushing the static oxidation material before the dynamic oxidation treatment, including: using a crusher to crush the static oxidation material to obtain a crushed material with a particle size D50 of 4-6μm, and the particle size D50 of the crushed material is, for example, 4μm, 4.5μm, 5μm, 5.5μm or 6μm, and any point value between any two of the above.

[0081] In the present invention, the static oxidation material is further crushed to increase the reaction surface area, each small particle can be fully in contact with the oxidizing gas, avoiding the problem of insufficient internal oxidation caused by large particles, and the crushed material with a particle size of 4-6μm has a shorter gas diffusion path, and the oxidizing gas can diffuse more quickly and evenly into each particle, which is conducive to improving the oxidation uniformity during dynamic oxidation. It can also better promote the formation of pore structure during dynamic oxidation, and the oxidation reaction is more likely to be initiated inside the particles, destroying the original structure of the long flame coal, forming more pore structures, and can better control the pore size and optimize the performance of the material.

[0082] In a preferred embodiment of the present invention, the temperature of the carbonization treatment is 1200-1600°C, for example, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, and any value therebetween.

[0083] Preferably, the carbonization treatment time is 1-10 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, and any value between any two of the above.

[0084] Preferably, the carbonization treatment is carried out in an inert atmosphere.

[0085] It should be noted that the present invention does not limit the gas in the inert atmosphere, and illustratively, it may be argon or nitrogen.

[0086] In a preferred embodiment of the present invention, the method for preparing the long flame coal-based hard carbon negative electrode material comprises: (1) First, the long flame coal is crushed to obtain granular coal with a particle size D50 of 20-50 μm, and then the granular coal is spread on a medium plate with a thickness of 8-15 mm by a flat plate method. The thickness of the granular coal layer after spreading is 3-4 mm. Then, the granular coal is placed in a static sintering device under an oxygen-containing atmosphere, heated to 100-250°C at a heating rate of 1-5°C / min, and then subjected to static oxidation treatment for 2-3 hours to obtain a static oxidized material; The oxygen-containing atmosphere of the static oxidation treatment includes an inert gas and an oxidizing gas, and the volume fraction of the inert gas is 60-85%; (2) The static oxidation material is crushed by a crusher to obtain a crushed material with a particle size D50 of 4-6 m, and then the crushed material is placed in a dynamic oxidation device under an oxygen-containing atmosphere, heated to 250-300°C at a heating rate of 1-5°C / min, and subjected to a primary treatment for 40-80 min, and then heated to 300-350°C at a heating rate of 1-5°C / min, and subjected to a secondary treatment for 40-80 min, and then heated to 350-400°C at a heating rate of 1-5°C / min, and subjected to a tertiary treatment for 40-80 min, completing the dynamic oxidation treatment process to obtain a long flame coal-based hard carbon negative electrode material precursor; The material filling rate of the dynamic oxidation equipment is 10-15%, the rotation speed of the dynamic oxidation equipment is 0.5-2rpm, the temperature of the primary treatment is less than the temperature of the secondary treatment and less than the temperature of the tertiary treatment, and the oxygen-containing atmosphere of the dynamic oxidation treatment includes inert gas and oxidizing gas, and the volume fraction of the inert gas is 80-90%; (3) In an inert atmosphere, the temperature is raised to 1200-1600° C. at a heating rate of 1-10° C. / min, and the long flame coal-based hard carbon negative electrode material precursor is carbonized for 1-10 h to obtain the long flame coal-based hard carbon negative electrode material.

[0087] According to a second aspect of the present invention, a long flame coal-based hard carbon negative electrode material is provided. The long flame coal-based hard carbon negative electrode material is prepared by the preparation method described in the first aspect.

[0088] According to a third aspect of the present invention, a sodium ion battery is provided, wherein the negative electrode of the sodium ion battery comprises the long flame coal-based hard carbon negative electrode material as described in the second aspect.

[0089] Example The present invention is further described in detail below in conjunction with the embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0090] In the following examples, unless otherwise specified, all raw materials are commercially available products.

[0091] Example 1 This embodiment provides a method for preparing a long flame coal-based hard carbon negative electrode material, and its preparation process flow chart is as follows: Figure 1 As shown, the preparation method comprises the following steps: (1) The long flame coal raw material is first pulverized to obtain granular coal with a particle size D50 of 35 μm, and then spread on a medium plate with a thickness of 10 mm by a flat plate method. The thickness of the granular coal layer after spreading is 3.5 mm. Then, it is placed in a mesh belt furnace under an oxygen-containing atmosphere, heated to 175°C at a heating rate of 3°C / min, and then subjected to static oxidation treatment for 2.5 hours to obtain a static oxidized material; The dielectric plate is a ceramic plate, the oxygen-containing atmosphere includes nitrogen and oxygen, and the volume fraction of nitrogen is 78%; (2) The static oxidation material is pulverized by a pulverizer to obtain a pulverized material with a particle size D50 of 5 μm, and then the pulverized material is placed in a rotary kiln under an oxygen-containing atmosphere, heated to 275°C at a heating rate of 3°C / min, and subjected to a primary treatment for 60 minutes, and then heated to 325°C at a heating rate of 3°C / min, and subjected to a secondary treatment for 60 minutes, and then heated to 375°C at a heating rate of 3°C / min, and subjected to a tertiary treatment for 60 minutes, completing the dynamic oxidation treatment process to obtain a long flame coal-based hard carbon negative electrode material precursor; The material filling rate of the rotary kiln is 12%, the rotation speed of the rotary kiln is 1 rpm, the oxygen-containing atmosphere includes nitrogen and oxygen, and the volume fraction of nitrogen is 85%; (3) In a nitrogen atmosphere, the temperature is raised to 1400° C. at a heating rate of 5° C. / min, and the long flame coal-based hard carbon negative electrode material precursor is carbonized for 5 hours to obtain the long flame coal-based hard carbon negative electrode material.

[0092] Example 2 This embodiment provides a method for preparing a long flame coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) The long flame coal raw material is first pulverized to obtain granular coal with a particle size D50 of 20 μm, and then spread on a medium plate with a thickness of 8 mm by a flat plate method. The thickness of the granular coal layer after spreading is 3 mm. Then, it is placed in a box furnace under an oxygen-containing atmosphere, heated to 100°C at a heating rate of 1°C / min, and then subjected to static oxidation treatment for 3 hours to obtain a static oxidized material; The medium plate is mullite, the oxygen-containing atmosphere includes nitrogen and oxygen, and the volume fraction of nitrogen is 85%; (2) The static oxidation material is pulverized by a pulverizer to obtain a pulverized material with a particle size D50 of 4 μm, and then the pulverized material is placed in a rotary kiln under an oxygen-containing atmosphere, heated to 250°C at a heating rate of 1°C / min, and subjected to a primary treatment for 80 minutes, and then heated to 300°C at a heating rate of 1°C / min, and subjected to a secondary treatment for 80 minutes, and then heated to 350°C at a heating rate of 1°C / min, and subjected to a tertiary treatment for 80 minutes, completing the dynamic oxidation treatment process to obtain a long flame coal-based hard carbon negative electrode material precursor; The material filling rate of the rotary kiln is 10%, the rotation speed of the rotary kiln is 0.5 rpm, the oxygen-containing atmosphere includes nitrogen and oxygen, and the volume fraction of nitrogen is 90%; (3) In a nitrogen atmosphere, the temperature is raised to 1200° C. at a heating rate of 1° C. / min, and the long flame coal-based hard carbon negative electrode material precursor is carbonized for 10 hours to obtain the long flame coal-based hard carbon negative electrode material.

[0093] Example 3 This embodiment provides a method for preparing a long flame coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) The long flame coal raw material is first pulverized to obtain granular coal with a particle size D50 of 20 μm, and then spread on a medium plate with a thickness of 15 mm by a flat plate method. The thickness of the granular coal layer after spreading is 4 mm. Then, it is placed in a coke oven under an oxygen-containing atmosphere, heated to 250°C at a heating rate of 5°C / min, and then subjected to static oxidation treatment for 3 hours to obtain a static oxidized material; The medium plate is mullite, the oxygen-containing atmosphere includes nitrogen and oxygen, and the volume fraction of nitrogen is 60%; (2) The static oxidation material is pulverized by a pulverizer to obtain a pulverized material with a particle size D50 of 6 μm, and then the pulverized material is placed in a rotary kiln under an oxygen-containing atmosphere, heated to 300°C at a heating rate of 5°C / min, and subjected to a primary treatment for 40 minutes, and then heated to 350°C at a heating rate of 5°C / min, and subjected to a secondary treatment for 40 minutes, and then heated to 400°C at a heating rate of 5°C / min, and subjected to a tertiary treatment for 40 minutes, completing the dynamic oxidation treatment process to obtain a long flame coal-based hard carbon negative electrode material precursor; The material filling rate of the rotary kiln is 15%, the rotation speed of the rotary kiln is 2 rpm, the oxygen-containing atmosphere includes nitrogen and oxygen, and the volume fraction of nitrogen is 80%; (3) In a nitrogen atmosphere, the temperature is raised to 1600° C. at a heating rate of 10° C. / min, and the long flame coal-based hard carbon negative electrode material precursor is carbonized for 1 hour to obtain the long flame coal-based hard carbon negative electrode material.

[0094] Example 4 The difference between this embodiment and embodiment 1 is that the volume fraction of nitrogen in the oxygen-containing atmosphere used in the static oxidation treatment and the dynamic oxidation treatment is 95%.

[0095] The rest of the preparation methods and parameters were the same as those in Example 1.

[0096] Example 5 The difference between this embodiment and embodiment 1 is that the volume fraction of nitrogen in the oxygen-containing atmosphere used in the static oxidation treatment is 85%.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Example 6 The difference between this embodiment and embodiment 1 is that the volume fraction of nitrogen in the oxygen-containing atmosphere used in the static oxidation treatment is 60%.

[0099] The rest of the preparation methods and parameters were the same as those in Example 1.

[0100] Example 7 The difference between this embodiment and embodiment 1 is that the volume fraction of nitrogen in the oxygen-containing atmosphere used in the dynamic oxidation treatment is 80%.

[0101] The rest of the preparation methods and parameters were the same as those in Example 1.

[0102] Example 8 The difference between this embodiment and embodiment 1 is that the volume fraction of nitrogen in the oxygen-containing atmosphere used in the dynamic oxidation treatment is 90%.

[0103] The rest of the preparation methods and parameters were the same as those in Example 1.

[0104] Example 9 The difference between this embodiment and embodiment 1 is that the temperature of the static oxidation treatment is 80°C.

[0105] The rest of the preparation methods and parameters were the same as those in Example 1.

[0106] Example 10 The difference between this embodiment and embodiment 1 is that the temperature of the static oxidation treatment is 300°C.

[0107] The rest of the preparation methods and parameters were the same as those in Example 1.

[0108] Embodiment 11 The difference between this embodiment and embodiment 1 is that the temperature of the static oxidation treatment is 100°C.

[0109] The rest of the preparation methods and parameters were the same as those in Example 1.

[0110] Example 12 The difference between this embodiment and embodiment 1 is that the temperature of the static oxidation treatment is 250°C.

[0111] The rest of the preparation methods and parameters were the same as those in Example 1.

[0112] Embodiment 13 The difference between this embodiment and embodiment 1 is that the material filling rate of the rotary kiln is 5%.

[0113] The rest of the preparation methods and parameters were the same as those in Example 1.

[0114] Embodiment 14 The difference between this embodiment and embodiment 1 is that the material filling rate of the rotary kiln is 20%.

[0115] The rest of the preparation methods and parameters were the same as those in Example 1.

[0116] Embodiment 15 The difference between this embodiment and embodiment 1 is that the material filling rate of the rotary kiln is 10%.

[0117] The rest of the preparation methods and parameters were the same as those in Example 1.

[0118] Example 16 The difference between this embodiment and embodiment 1 is that the material filling rate of the rotary kiln is 15%.

[0119] The rest of the preparation methods and parameters were the same as those in Example 1.

[0120] Embodiment 17 The difference between this embodiment and embodiment 1 is that the rotation speed of the rotary kiln is 0.1 rpm.

[0121] The rest of the preparation methods and parameters were the same as those in Example 1.

[0122] Embodiment 18 The difference between this embodiment and embodiment 1 is that the rotation speed of the rotary kiln is 5 rpm.

[0123] The rest of the preparation methods and parameters were the same as those in Example 1.

[0124] Embodiment 19 The difference between this embodiment and embodiment 1 is that the rotation speed of the rotary kiln is 0.5 rpm.

[0125] The rest of the preparation methods and parameters were the same as those in Example 1.

[0126] Embodiment 20 The difference between this embodiment and embodiment 1 is that the rotation speed of the rotary kiln is 2 rpm.

[0127] The rest of the preparation methods and parameters were the same as those in Example 1.

[0128] Embodiment 21 The difference between this embodiment and embodiment 1 is that the temperature of the primary treatment in the dynamic oxidation treatment is 200°C.

[0129] The rest of the preparation methods and parameters were the same as those in Example 1.

[0130] Embodiment 22 The difference between this embodiment and embodiment 1 is that the temperature of the primary treatment in the static oxidation treatment is 250°C.

[0131] The rest of the preparation methods and parameters were the same as those in Example 1.

[0132] Embodiment 23 The difference between this embodiment and embodiment 1 is that the temperature of the primary treatment in the dynamic oxidation treatment is 300°C.

[0133] The rest of the preparation methods and parameters were the same as those in Example 1.

[0134] Embodiment 24 The difference between this embodiment and embodiment 1 is that the temperature of the third-stage treatment in the dynamic oxidation treatment is 450°C.

[0135] The rest of the preparation methods and parameters were the same as those in Example 1.

[0136] Embodiment 25 The difference between this embodiment and embodiment 1 is that the temperature of the third-stage treatment in the dynamic oxidation treatment is 350°C.

[0137] The rest of the preparation methods and parameters were the same as those in Example 1.

[0138] Embodiment 26 The difference between this embodiment and embodiment 1 is that the temperature of the tertiary treatment in the dynamic oxidation treatment is 400°C.

[0139] The rest of the preparation methods and parameters were the same as those in Example 1.

[0140] Embodiment 27 The difference between this embodiment and embodiment 1 is that only a single-stage treatment is performed in the dynamic oxidation treatment, the temperature is increased to 325° C. at a heating rate of 3° C. / min, and the dynamic treatment is performed for 180 minutes.

[0141] The rest of the preparation methods and parameters were the same as those in Example 1.

[0142] Comparative Example 1 The difference between this comparative example and Example 1 is that no static oxidation treatment process is performed, and only a dynamic oxidation treatment process is performed.

[0143] The rest of the preparation methods and parameters were the same as those in Example 1.

[0144] Comparative Example 2 The difference between this comparative example and Example 1 is that no dynamic oxidation treatment process is performed, and only a static oxidation treatment process is performed.

[0145] The rest of the preparation methods and parameters were the same as those in Example 1.

[0146] Performance Testing 1. The microstructure of the long flame coal-based hard carbon negative electrode material prepared in Example 1 was characterized, and its SEM image is as follows: Figure 2 shown.

[0147] 2. The long flame coal-based hard carbon negative electrode material provided in the above embodiment and comparative example is made into a negative electrode sheet, and the preparation method of the negative electrode sheet comprises: mixing and slurrying the prepared hard carbon, conductive carbon black (Super P), carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) according to a formula ratio of 91:2:2:5. The prepared slurry is scraped on the carbon-coated copper foil, and then transferred to a 65°C forced air drying oven until the electrode sheet is dry (about 1-2 h), and then transferred to a vacuum drying oven for drying for 12 h to obtain a negative electrode sheet.

[0148] Then, the negative electrode sheet is assembled with the positive electrode sheet (NEPP), the separator (cellulose separator) and the electrolyte (TC-ENA28D) to obtain a sodium-ion battery.

[0149] The above sodium ion batteries were subjected to electrochemical performance tests, including capacity performance, initial efficiency and cycle performance.

[0150] (1) The test conditions for capacity performance and first efficiency are: discharge at 0.1C to 0V, let stand for 5 minutes, then charge at 0.1C to 2.0V. The test temperature is 25°C (2) The test conditions for cycle performance are: let stand for 10 minutes, then charge at 0.2C, let stand for 10 minutes, and then charge at 0.2C for cycle test. The test temperature is 25°C, and the capacity retention rate after 100 cycles is tested.

[0151] The test results are shown in Table 1.

[0152] Table 1 Test results of Examples 1-27 and Comparative Examples 1-2

[0153] analyze: It can be seen from the above table that the present invention can achieve full oxidation of long flame coal in all directions and at multiple points by means of static and dynamic combined oxidation, thereby improving the oxidation uniformity and oxidation depth inside the coal particles. The long flame coal-based hard carbon negative electrode material prepared by this method has high reactivity, and the sites of grafted oxygen inside the particles can promote the formation of a "house of cards" structure, so that it exhibits high reversible capacity, high first coulombic efficiency and excellent cycle performance.

[0154] It can be seen from Example 1 and Examples 4-8 that if the volume fraction of nitrogen in the oxygen-containing atmosphere of static oxidation treatment is too large, it will affect the grafting effect of the molecular structure of coal-based condensed aromatic hydrocarbons and oxygen, and the long flame coal will be difficult to fully oxidize, resulting in poor reversible capacity and first efficiency of the formed hard carbon; when the volume fraction of nitrogen in the oxygen-containing atmosphere of dynamic oxidation treatment is greater than that of static oxidation treatment, it is beneficial to form more pore structures and more through-pore structures, which is beneficial to improve the capacity and rate properties of hard carbon negative electrode materials.

[0155] It can be seen from Example 1 and Examples 9-12 that if the temperature of the static oxidation treatment is too low, the carbon on the surface of the long flame coal is difficult to be fully oxidized, and the carbon structure on part of the surface is not destroyed, resulting in that it is difficult for oxygen molecules to penetrate into the interior of the particles during the subsequent dynamic oxidation process, resulting in a low reversible capacity of the hard carbon; if the temperature of the static oxidation treatment is too high, it is easy to cause ablation on the surface of the long flame coal particles, resulting in excessive oxidation in the subsequent dynamic oxidation process, resulting in a low initial efficiency of the hard carbon.

[0156] It can be seen from Example 1 and Examples 13-16 that if the material filling rate of the rotary kiln is too low, the production capacity of hard carbon preparation will be affected; if the material filling rate of the rotary kiln is too high, although the production capacity of hard carbon preparation can be improved, the contact effect between the long flame coal and the oxidizing medium is poor, which affects the oxidation effect, resulting in lower reversible capacity and first efficiency.

[0157] It can be seen from Examples 1 and 17-20 that if the rotation speed of the rotary kiln is too low, the long flame coal material will stay in the rotary kiln for a long time, which may easily cause excessive oxidation; if the rotation speed of the rotary kiln is too high, the contact time between the long flame coal particles and the oxidizing medium will be short, and the molecular structure of the polycyclic aromatic hydrocarbons in the long flame coal will not be fully grafted with oxygen, which will affect the reversible capacity and first-effect properties of the hard carbon.

[0158] It can be seen from Example 1 and Examples 21-23 that if the temperature of the primary treatment is too low, the reactivity of the long flame coal particles with oxygen is poor, resulting in a low reversible capacity.

[0159] It can be seen from Examples 1 and 24-26 that if the temperature of the tertiary treatment is too high, the long flame coal reacts too deeply with oxygen, affecting the formation of the "house of cards" structure inside the hard carbon, thereby causing the hard carbon to have low reversible capacity and poor cycle performance.

[0160] It can be seen from Example 1 and Example 27 that if the dynamic oxidation is not carried out by multi-stage treatment, but only by secondary treatment, the reactivity of the long flame coal with the oxidizing medium is insufficient, resulting in poor reversible capacity and first efficiency of the hard carbon.

[0161] It can be seen from Example 1 and Comparative Example 1 that if the dynamic oxidation treatment process is not carried out, the surface of the long flame coal particles is not damaged. Only under dynamic oxidation, the internal structure of the hard carbon cannot be completely oxidized, resulting in poor reversible capacity, first efficiency and cycle performance of the formed hard carbon.

[0162] It can be seen from Example 1 and Comparative Example 2 that if the dynamic oxidation treatment process is not carried out, the long flame coal particles are only oxidized statically. Under such conditions, only the surface of the long flame coal particles is oxidized, and no deep oxidation occurs inside the particles. The "house of cards" configuration required for hard carbon cannot be formed, and the reversible capacity, first effect and cycle performance of the hard carbon are poor.

[0163] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a long flame coal-based hard carbon negative electrode material, characterized in that: The preparation method comprises: Firstly, static oxidation treatment is performed on long flame coal to obtain static oxidation material; Then, the static oxidizing material is subjected to dynamic oxidation treatment to obtain a long flame coal-based hard carbon negative electrode material precursor; Then, the long flame coal-based hard carbon negative electrode material precursor is carbonized to obtain the long flame coal-based hard carbon negative electrode material; Wherein, the long flame coal is in powder form.

2. The preparation method according to claim 1, characterized in that The static oxidation treatment adopts a flat plate method, including: firstly, the long flame coal is spread flat on a medium plate, and then placed in a static sintering device for static oxidation treatment; The layer thickness of the long flame coal after being laid flat is 3-4 mm.

3. The preparation method according to claim 1, characterized in that: The static oxidation treatment process is carried out in an oxygen-containing atmosphere, wherein the oxygen-containing atmosphere of the static oxidation treatment includes an inert gas and an oxidizing gas, and the volume fraction of the inert gas is 60-85%.

4. The preparation method according to claim 1, characterized in that: The temperature of the static oxidation treatment is 100-250°C, the heating rate is 1-5°C / min, and the constant temperature time is 2-3h.

5. The preparation method according to claim 1, characterized in that: The dynamic oxidation treatment includes primary treatment, secondary treatment and tertiary treatment, and the temperature of the primary treatment is less than the temperature of the secondary treatment and less than the temperature of the tertiary treatment.

6. The preparation method according to claim 5, characterized in that: The temperature of the primary treatment is 250-300°C, and the time is 40-80min; the temperature of the secondary treatment is 300-350°C, and the time is 40-80min; the temperature of the tertiary treatment is 350-400°C, and the time is 40-80min.

7. The preparation method according to claim 1, characterized in that: The dynamic oxidation treatment process is carried out in a dynamic oxidation device; The material filling rate of the dynamic oxidation equipment is 10-15%; The rotation speed of the dynamic oxidation device is 0.5-2rpm; The dynamic oxidation treatment is performed in an oxygen-containing atmosphere.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The temperature of the carbonization treatment is 1200-1600°C, and the time of the carbonization treatment is 1-10h; The carbonization treatment is carried out in an inert atmosphere.

9. A long flame coal-based hard carbon negative electrode material, characterized in that: The long flame coal-based hard carbon negative electrode material is prepared by the preparation method according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the long flame coal-based hard carbon negative electrode material as claimed in claim 9.

Citation Information

Cited By

  • Preparation method and device of sodium battery negative electrode material based on long flame coal

    CN121134740A